Ratoon rice strategy for enhanced water resource management: A simulation-based study in tropical monsoon climates - Shutaro Shiraki; Kywae; Nwe Ni; Thin Mar Cho; Aung Kyaw Thu; Naoki Horikawa (Agricultural Water Management)
Rice-ratoon rice double cropping (RR) offers a substantial reduction in labor and resource inputs while significantly enhancing water use efficiency compared to conventional double cropping (DR). This system holds promises in tropical monsoon regions with limited water resources. However, the differences in irrigation periods and water requirements between DR and RR call for region-specific water resource management. This study evaluated the potential of introducing RR on reservoir management in tropical monsoon climates, simulating its effects using 23 years of hydrological data. The findings show that starting RR in early June can cut irrigation supply by up to 51 %, boost water productivity by 60–87 % compared to DR, and sustain a high reservoir reliability index. Yet, challenges persist, including the complexities of mechanical harvesting during the monsoon season and the risk of yield reduction due to delayed crop cultivation. While triple cropping with rice and two ratoons (RRR) is possible, it demonstrated lower water productivity and was less effective in water resource management than other cropping patterns. Despite RR’s potential to enhance water use efficiency in tropical monsoon regions, further research and technical advancements are needed for practical application. This study offers valuable insights into sustainable rice production and water resource management in water-scarce regions.